The correlation between thermal comfort in buildings and fashion products - Giesel, Aline; Souza, Patricia de Mello [UNESP] (IOS Press, 2012)
This article is about thermal comfort in the wearable product. The research correlates fashion and architecture, in so far as it elects the brise soleil - an architectural element capable of regulating temperature and ventilation inside buildings - as a study referential, in trying to transpose and adapt its mechanisms to the wearable apparel.
Keywords: Fashion design; Pattern Making; Ergonomics; Thermal comfort; Architecture